Fostering resilience and well-being in children and families in poverty: why hope still matters - Valerie Maholmes (Oxford University Press, 2014)
"In Fostering Resilience and Well-being in Children and Families in Poverty, Dr. Valerie Maholmes sheds light on the mechanisms and processes that enable children and families to manage and overcome adversity"--